Microwave attenuation of fresh Hevea latex - Khalid, Kaida; Abd. Wahab, Mahdi (Rubber Research Institute of Malaysia, 1984)
The relationship between microwave attenuated power and dry rubber content of fresh Hevea latex is derived. This calculation is based on a model of water suspension by Wiener. Calculation showed that the dry rubber content of Hevea latex can be determined from conveniently measured parameters such as microwave attenuation, density of latex and thickness of latex layer. The experimental results on attenuation as a function of dry rubber content agree with data calculated from the theory within experimental uncertainty